Some notes on a workshop on a Feed Resource Assessment in Smallholder Systems - Adie, Aberra (International Livestock Research Institute, 2009)
A small group met for three days with the aim of developing a simple tool for characterizing the smallholder feeding system in different environments. The vision was to produce something that would be useful for development agencies to diagnose feed issues and provide guidance for potential interventions. With this in mind, the group included participants from the NGO sector (BAIF and Himothan) to maintain the focus of the researchers making up the rest of the group, on producing something practical.